'Understanding Disability': Evaluating a contact-based approach to enhancing attitudes and disability literacy of medical students. Issue 1 (January 2019) - Lynch, Julie; Last, Jason; Dodd, Philip; Stancila, Daniela; Linehan, Christine
Abstract: Background: Health disparities and disparities in the provision of healthcare to people with disabilities remains a topic of concern. Research demonstrates that attitudes of healthcare providers contribute to this disparity. The approach to disability education and training in medical school warrants evaluation. Objectives: This study sought to investigate the efficacy of an educational intervention in cultivating positive attitudes towards disability in medical students, and determine the specific impact of an interaction-based hospital visit to patients undergoing neurological rehabilitation. Methods: Web-based questionnaires were distributed to medical students undertaking a 12-week 'Understanding Disability' module. Measures of anxiety, attitude, competency and empathy were obtained from 65 students at the beginning (T1), middle (T2) and end (T3) of the module. At T2, approximately half of the students had completed a hospital visit and half had not. Results: Scores changed significantly across all constructs between the beginning and end of the module suggesting a positive overall module effect. Findings confirmed a significant difference in anxiety and empathy levels between the group of students who had completed the visit to the rehabilitation hospital by the middle survey wave and those who had not, indicating a specific placement effect. Conclusions: Our findings suggest that interpersonal contact with individuals with disabilities has a distinct impact on the affective variables of anxiety and empathy. Previous research suggests that this contributes towards improved attitudes to disability. Overall, we provide strong evidence for the inclusion of contact-based educational interventions in medical school to enhance students' attitudes to disability.